High-level expression and purification of recombinant wheat germ agglutinin in Rachiplusia nu larvae - Urtasun, Nicolás (2015)
Wheat germ agglutinin (WGA) is a homodimeric lectin stabilized by non-covalent interactions. Each monomer of 171 residues, which has a complex structure with 16 disulfide bridges, determines two sites for the specific binding of N-acetyl-d-glucosamine and one for the specific binding of N-acetylneuraminic acid. Because of these folding requirements, the production of high yields of recombinant WGA is still not possible and its extraction from wheat germ is the only source for commercial purposes. This work reports for the first time the expression of WGA isolectin A (WGA A), using a baculovirus expression system in Sf9 cells and Rachiplusia nu larvae. High levels of recombinant WGA A were obtained in both cases, especially in R. nu, where yields reached 346.6 ± 88.5 μg/g of larvae. Also, an integrated purification method was developed based on aqueous two-phase separation coupled to affinity chromatography using chitosan mini-spheres. The recombinant WGA A was able to recognize ovoalbumin sugar moieties, cross-react with anti-WGA serum and agglutinate human red blood cells, and showed the same behavior as that of commercial WGA in SDS-PAGE and RP-HPLC analyses.